PERUBAHAN PERILAKU KONSUMTIF MASYARAKAT PASCA ISU RESESI EKONOMI GLOBAL TAHUN 2023 - Nur Farida; Lelli Kisdayanti; Nur Aini Anisa; Syamsul Arifin (Bajang Institute, 2024)
In 2023, the World Bank in its report entitled